P‐8.7: A Novel Multi‐layers PCB Design for UHD Display System. (4th October 2019) - Li, Xianzhen; li, Zhichao; Zhao, Tianyue; Guan, Enhui; Zhang, Xiao
Abstract : With the rapid development of video technology and the improvement of clients' requirement for video quality, high resolution and large‐format display has become an inevitable development trend for terminal display devices. Concerning about 8K products is becoming popular, products such as cameras, UAVs, broadcasters, editing equipments and display equipments are equipped with 8K display.The article mainly tells about the design of power supply for 8K UHD display system based on FPGA naming XC7K325T. The design of switching circuit and the key factors in the design of multi‐layer board power supply are described in detail, such as current carrying capacity calculation, power channel evaluation, protection, filtering and so on.